The phylogeny of robber flies (Asilidae) inferred from ultraconserved elements. (16th June 2021) - Cohen, Chris M.; Noble, Katherine; Jeffrey Cole, T.; Brewer, Michael S.
ABSTRACT: Robber or assassin flies (Asilidae) are a diverse family of venomous predators. The most recent classification organizes Asilidae into 14 subfamilies based on a morphological phylogeny, but many of these are not supported by molecular data. To test the monophyly of various clades in Asilidae, we used the recently developed Diptera‐wide ultraconserved element bait set to compile seven datasets comprising 151 robber flies and 145–2496 loci. We also compared the performance of various nodal support metrics. Our Maximum Likelihood phylogeny was fully resolved and well supported, but partially incongruent with the coalescent phylogeny. Further examination of datasets suggested that GC bias had influenced gene tree inference and subsequent species tree analyses. The subfamilies Brachyrhopalinae, Dasypogoninae, Dioctriinae, Stenopogoninae, Tillobromatinae, Trigonomiminae and Willistonininae were not recovered as monophyletic. The inter‐subfamily relationships are summarized as follows: Laphriinae and Dioctriinae (in part) successively sister to the remaining subfamilies, which form two clades: the first consists of a grade of Stenopogoninae (in part), Willistonininae (in part), Bathypogoninae+Phellinae, Stichopogoninae, Leptogastrinae, Ommatiinae and Asilinae; the second clade consists of a paraphyletic assemblage of genera from Dioctriinae (in part), Trigonomiminae, Stenopogoninae (in part), Tillobromatinae, Brachyrhopalinae and Dasypogoninae. This phylogeny demonstrates that the higher classification of Asilidae is far from settled, but does provide a much‐needed foundation for a thorough revision of the subfamily classification. Abstract : We use ultraconserved elements to assemble the largest and most comprehensive molecular dataset to date and demonstrate that half of the currently recognized subfamilies in Asilidae are not monophyletic. We outline the updates needed to make the subfamily classification consistent with our phylogeny but do not propose nomenclatural changes. After comparing the performance of various nodal support metrics in our dataset, we recommend that quartet concordance values be reported alongside bootstrap values in future phylogenomic studies.